Rural Labor and Rural Non-Agricultural Activities in the Philippines - Maria Teresa Sanchez-Robielos (Philippine Institute for Development Studies (PIDS), 1994)
This study examines the different aspects of labor in the rural household economy. It identifies the factors that significantly determine the labor allocation decisions of rural households. Moreover, it looks at how the availability and growth of rural nonagricultural employment opportunities affect the rural household allocation of labor and the rural labor markets. In addition, it makes use of labor market indicators to trace the labor market links between the agricultural and rural nonagricultural sectors.
Keywords: 330; labor market; agriculture sector; farm lands; nonfarm work; human capital